Determination of Tetracycline and Fluoroquinolone Antibiotics at Trace Levels in Sludge and Soil - Marie-Virginie Salvia; Maëva Fieu; Emmanuelle Vulliet (Applied and Environmental Soil Science)
This work describes the development of a sensitive analytical method to determine simultaneously traces of tetracycline and fluoroquinolone antibiotics in sludge and soil, based on PLE extraction, followed by SPE purification and finally an analysis by LC-MS/MS. Recoveries were greater than 87% in the case of fluoroquinolones and between 25.4 and 41.7% for tetracyclines. Low relative standard deviations (<15%) were obtained in both matrices. The limits of quantification were comprised between 1.1 and 4.6 ng/g and between 5 and 20 ng/g in soil and sludge, respectively. The method was then successfully applied to the analysis of the target antibiotics in sludge as well as soil that received spreading. The substances most frequently found and with the highest levels were fluoroquinolones with concentrations exceeding 1,000 ng/g in several samples of sludge and up to 16 ng/g in soil.